To find the value of f(-4), you substitute -4 for x in the equation f(x) = 10 - 4x:
f(-4) = 10 - 4(-4)
= 10 + 16
= 26
Therefore, the value of f(-4) is 26.
function is shown what is the value of f(-4) f(x)= 10-4x
11 answers
A function is shown what is the value of F (5)
F(x)=<-3+8x²
F(x)=<-3+8x²
To find the value of F(5), you substitute 5 for x in the equation F(x) = -3 + 8x².
F(5) = -3 + 8(5)²
= -3 + 8(25)
= -3 + 200
= 197
Therefore, the value of F(5) is 197.
F(5) = -3 + 8(5)²
= -3 + 8(25)
= -3 + 200
= 197
Therefore, the value of F(5) is 197.
function is shown what is the value of f (5)
f(x)=<-3+8x²
f(x)=<-3+8x²
To find the value of f(5), you substitute 5 for x in the equation f(x) = -3 + 8x².
f(5) = -3 + 8(5)²
= -3 + 8(25)
= -3 + 200
= 197
Therefore, the value of f(5) is 197.
f(5) = -3 + 8(5)²
= -3 + 8(25)
= -3 + 200
= 197
Therefore, the value of f(5) is 197.
A pizza shop owner determine the annual profit in dollars from selling pizzas using p(n) = 32n - 0.04n² where in is the number of pizza's sold what is the annual profit if the pizza shop owner sells $350 pizzas
To find the annual profit if the pizza shop owner sells 350 pizzas, you substitute n = 350 into the equation p(n) = 32n - 0.04n²:
p(350) = 32(350) - 0.04(350)²
= 11200 - 0.04(122500)
= 11200 - 4900
= 6300
Therefore, the annual profit if the pizza shop owner sells 350 pizzas is $6,300.
p(350) = 32(350) - 0.04(350)²
= 11200 - 0.04(122500)
= 11200 - 4900
= 6300
Therefore, the annual profit if the pizza shop owner sells 350 pizzas is $6,300.
A sequence can be generated by using an=3a(n-1) where a1=3 and n is a whole number greater than 1. What are the four term in this sequence?
Using the given recursive formula for the sequence, we can find the first four terms as follows:
a1 = 3
a2 = 3 * a(2-1) = 3 * a1 = 3 * 3 = 9
a3 = 3 * a(3-1) = 3 * a2 = 3 * 9 = 27
a4 = 3 * a(4-1) = 3 * a3 = 3 * 27 = 81
Therefore, the first four terms in this sequence are: 3, 9, 27, 81.
a1 = 3
a2 = 3 * a(2-1) = 3 * a1 = 3 * 3 = 9
a3 = 3 * a(3-1) = 3 * a2 = 3 * 9 = 27
a4 = 3 * a(4-1) = 3 * a3 = 3 * 27 = 81
Therefore, the first four terms in this sequence are: 3, 9, 27, 81.
A sequence can be generated by using an=3a(n-1) where a1=6 and n is a whole number greater than 1. What are the four term in this sequence?
Using the given recursive formula for the sequence, we can find the first four terms as follows:
a1 = 6
a2 = 3 * a(2-1) = 3 * a1 = 3 * 6 = 18
a3 = 3 * a(3-1) = 3 * a2 = 3 * 18 = 54
a4 = 3 * a(4-1) = 3 * a3 = 3 * 54 = 162
Therefore, the first four terms in this sequence are: 6, 18, 54, 162.
a1 = 6
a2 = 3 * a(2-1) = 3 * a1 = 3 * 6 = 18
a3 = 3 * a(3-1) = 3 * a2 = 3 * 18 = 54
a4 = 3 * a(4-1) = 3 * a3 = 3 * 54 = 162
Therefore, the first four terms in this sequence are: 6, 18, 54, 162.